2019
DOI: 10.1093/schbul/sbz060
|View full text |Cite
|
Sign up to set email alerts
|

Synapse Pathology in Schizophrenia: A Meta-analysis of Postsynaptic Elements in Postmortem Brain Studies

Abstract: Changed synapse density has been suggested to be involved in the altered brain connectivity underlying schizophrenia (SCZ) pathology. However, postmortem studies addressing this topic are heterogeneous and it is not known whether changes are restricted to specific brain regions. Using meta-analysis, we systematically and quantitatively reviewed literature on the density of postsynaptic elements in postmortem brain tissue of patients with SCZ compared to healthy controls. We included 3 outcome measurements for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 98 publications
(110 reference statements)
12
85
0
Order By: Relevance
“…Neuroimaging and post-mortem studies of individuals with SCZ or BD show reduced brain volume and spine density, particularly in the prefrontal and anterior cingulate cortex and hippocampus relative to healthy controls [1][2][3][4] . These changes coincide with reduced protein and/or mRNA levels of various synaptic markers [5][6][7][8][9][10][11] . Whereas the majority of these data were derived from post-mortem human material, the recent development of the UCB-J PET tracers, which specifically interact with the presynaptic Synaptic Vesicle glycoprotein 2A (SV2A), has enabled visualisation of pre-synaptic terminal density in the living human brain [12][13][14] .…”
Section: Introductionmentioning
confidence: 92%
“…Neuroimaging and post-mortem studies of individuals with SCZ or BD show reduced brain volume and spine density, particularly in the prefrontal and anterior cingulate cortex and hippocampus relative to healthy controls [1][2][3][4] . These changes coincide with reduced protein and/or mRNA levels of various synaptic markers [5][6][7][8][9][10][11] . Whereas the majority of these data were derived from post-mortem human material, the recent development of the UCB-J PET tracers, which specifically interact with the presynaptic Synaptic Vesicle glycoprotein 2A (SV2A), has enabled visualisation of pre-synaptic terminal density in the living human brain [12][13][14] .…”
Section: Introductionmentioning
confidence: 92%
“…Synaptophysin is enriched in presynaptic nerve terminals 21 where, along with synaptobrevin and SV2A, it is involved in regulating vesicle exocytosis into synapses 22,23 . Recent metaanalyses of post-mortem studies showed significantly lower synaptophysin levels in the frontal and cingulate cortices and hippocampus with moderate-to-large effect size 8 and lower postsynaptic element levels in schizophrenia relative to controls 24 . Furthermore, human-derived neural cultures have shown elevated, complement-dependent elimination of synaptic structures 25 , lower neurite number and neuronal connectivity 26 and synaptic vesicle release deficits 27 in schizophrenia relative to healthy controls.…”
mentioning
confidence: 99%
“…Lastly, SCZ enrichment for both excitatory and inhibitory neurons were similar to those of AD, possessing unique, diseasespecific interactions. For excitatory neurons, we observed neurotransmitter-based signal transmission (p<1.11e-13) [56] as well as regulation of trans-synaptic signaling (p<1.46e-29) [45], synapse structure and activity (p<1.02e-15) [49], and glutamate receptor signaling (p<3.90e-12) [41]. From the inhibitory neuron standpoint, SCZ enrichment shared multiple enrichment terms with AD, suggesting abstraction from standard disease-specific pathology and broader atypical neuronal signaling and activity.…”
Section: Excitatory Microgliamentioning
confidence: 86%
“…In SCZ, then, at a neuroimmune response level, we found that multiple key hallmark pathways were implicated, including dopaminergic synapse p(<7.78e-9) [40,41], and signaling by both Receptor Tyrosine Kinase (p<1.86e-10) [42,43] and cGMP-PKG (p<2.94e-7) [44]. From an oligodendrocyte-based context, we observed that multiple forms of synapse function and regulation were enriched -specifically, the regulation of trans-synaptic signaling (p<1.95e-8) [45], modulation of chemical synaptic transmission (p<1.80e-8) [46], and neuron-to-neuron synapses (p<2.57e-11) [47]. The overarching theme of these observations concerns furthered impacts on signaling and transmission between neurons which Schizophrenia pathology widely believes to be implicated [45,46,48,49].…”
Section: Excitatory Microgliamentioning
confidence: 91%
See 1 more Smart Citation